Study of new modifiable clamp design to fit all teeth (in vitro study) - الجبيلي سومر; باسم سليم (Latakia University Journal -Medical Sciences Series, 2024)
This study aims to test a new modifiable clamp design to fit all teeth, Therefore, a sample of 60 gypsum casts was taken to people whose ages ranged between 22-50 years. The mesiodistal dimension was measured at the cervical clinical line of each tooth (C-MDs) from both the buccal and lingual sides, then a modified clamp was manufacture. The manufacturing of the modified clamp depends on the clamp # 200 and a skeletal screw, then the (C-MDs of the teeth) were compared with the mesiodistal dimension of the clamps from (Elite™, Medixdent) and the range of mesiodistal dimension of the modified clamp, and a comparison was made between The tensile strength of the previous clamps with the tensile strength of the modified clamp after being applied to the teeth . (11#,14#,16#,41#,44#,46) the tensile strength was measured by a tensile tester (testometric, 350.1kN, China) and statistical analyzes were conducted, such as (simple T-test) and (paired sample T-test) The study reached a number of results, including: There is no statistically significant difference between the C-MDs for men and women and between the C-MDs for opposing teeth on the right and left sides. There is a statistically significant difference between the average C - MDs of the teeth and the width of the most suitable clasps for them, except for the #207 clasp. It was suitable for (C-MDs) of the maxillary second premolars. The mesiolateral dimension of the modified clasp includes the (C-MDs) for all teeth except the first and second mandibular molars. The tensile strength of all clasps is restricted. The study is smaller than the results of the tensile strength of the modified clamp.